INTERNET-BASED INFORMATION DISCLOSURE PRACTICES: DOES REPUTATION OF AUDITOR MATTERS? - Nurrachma, Claudia Sheva; Sumarta, Nurmadi Harsa; Bandi, Bandi (TEMA, 2023)
This study aims to examine the Internet-based information disclosure in financial companies listed on the Indonesia Stock Exchange (IDX) by examining profitability, leverage, age, companies size, growth, performance, auditor’s reputation and firm performance audited by Big four as companies characteristics and for website characteristics by general and financial companies information, company news or event and financial and corporate governance internet based report. The population of this study is financial companies listed on the Indonesia Stock Exchange between the years of 2011-2013, while the samples consist of 210 companies. This research uses a secondary data derives from the annual reports and corporate website. The technique used to test the hypothesis is multiple linear regression analysis techniques. The results indicate that auditor reputation, firm performance and firm performance audited by Big four has no effect because the company's performance is not only influenced by the auditor but the manager and administrator of the company's website do not involve auditors in disclosure financial information of the internet based. The study also finds that leverage and size firm has a significant effect on the study through internet-based information disclosure. In contrast, profitability, age, growth does not have a significant influence on this study.